Pengaruh Pendapatan Premi, Beban Klaim, Risk Based Capital, Investasi dan Dividen Terhadap Profitabilitas - Minah Handriani; Abubakar Arif (Publikasi Indonesia, 2022)
This study aims to analyze the effect of earnings premium, claim expense, risk based capital, investment and dividends on profitbility general insurance company listed on the Indonesia Stock Exchange for the 2017-2021 period. This study uses secondary data obtained from the financial reports and annual reports of each company. The number of samples used was 12 general insurance company on the Indonesia Stock Exchange for the 2017-2021 period. The sampling technique used was purposive sampling with multiple linear regression analysis method with panel data. The analytical tool used in this study is Eviews. The results of research using multiple linear regression analysis with panel data show that: (1) earnings premium has a positive effect on profitbility, (2) claim expense has a negative effect on profitbility, (3) risk based capital has a positive effect on profitbility, (4) investment has a positive effect on profitbility, (5) dividends has a negative effect on profitability.